(3eONd eYGUQs - (3SeQ Jhajb(B, (3UHQIs ((3YeGf(B:s (3OGQ GdGYUGQ GdYdej(B,s, 2010)
(3ebOeI aj GdJShjb , GdHjFI GdJShjbjI , JbSje GdShb , Sdhc GdeSJgdc , SjGSGJ h bQGQdJ GdSdY , JWhjQ GdSdY GdLOjOI , GdJSYjQ , GdJhRjY , GdJQhjL , GdJShjb GdGdcJQhfj (B.s
(3eQGLY U(B.231s
Keywords: (3COGQI GdeHjYGJs; (3GdHjFI GdJShjbjIs; (3GdJShjbs; (3GdJShjb GdGdcJQhfjs